TRACING NITROGEN IN VOLCANIC AND GEOTHERMAL VOLATILES FROM THE NICARAGUAN VOLCANIC FRONT - Elkins L.J.; Fischer T.P.; Sharp Z.D.; Hilton D.R.; McKnight S.; Walker J. (My University, 2006)
We report new chemical and isotopic data from 26 volcanic and geothermal gases, vapor condensates, and thermal water samples, collected along the Nicaraguan volcanic front. The samples were analyzed for chemical abundances and stable isotope compositions, with a focus on nitrogen abundances and isotope ratios. These data are used to evaluate samples for volatile contributions from magma, air, air-saturated water, and the crust. Samples devoid of crustal contamination (based upon He isotope composition) but slightly contaminated by air or air-saturated water are corrected using N2/Ar ratios in order to obtain primary magmatic values, composed of contributions from upper mantle and subducted hemipelagic sediment on the down-going plate. Using a mantle endmember with δ15N = -5‰ and N2/He = 100 and a subducted sediment component with δ15N = +7‰ and N2/He = 10,500, the average sediment contribution to Nicaraguan volcanic and geothermal gases was determined to be 71%. Most of the gases were dominated by sediment-derived nitrogen, but gas from Volcán Mombacho, the southernmost sampling location, had a mantle signature (46% from subducted sediment, or 54% from the mantle) and an affinity with mantle-dominated gases discharging from Costa Rica localities to the south. High CO2/N2 exc. ratios (N2 exc. is the N2 abundance corrected for contributions from air) in the south are similar to those in Costa Rica, and reflect the predominant mantle wedge input, whereas low ratios in the north indicate contribution by altered oceanic crust and/or preferential release of nitrogen over carbon from the subducting slab. Sediment-derived nitrogen fluxes at the Nicaraguan volcanic front, estimated by three methods, are 7.8 × 108 mol N/a from 3He flux, 6.9 × 108 mol/a from SO2 flux, and 2.1 × 108 and 1.3 × 109 mol/a from CO2 fluxes calculated from 3He and SO2, respectively. These flux results are higher than previous estimates for Central America, reflecting the high sediment-derived volatile contribution and the high nitrogen content of geothermal and volcanic gases in Nicaragua. The fluxes are also similar to but higher than estimated hemipelagic nitrogen inputs at the trench, suggesting addition of N from altered oceanic basement is needed to satisfy these flux estimates. The similarity of the calculated input of N via the trench to our calculated outputs suggests that little or none of the subducted nitrogen is being recycled into the deeper mantle, and that it is, instead, returned to the surface via arc volcanism. © 2006 Elsevier Inc. All rights reserved.